2000
DOI: 10.1007/s001980070080
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Versus Longitudinal Evaluation of Bone Loss in Men and Women

Abstract: We evaluated age- and sex-specific differences in bone density at a variety of skeletal sites in a population-based sample of 348 men (age 22-90 years) and 351 women (age 21-93 years) by dual-energy X-ray absorptiometry. Several patterns of age-related bone loss were observed, but adjustments for height (or, where possible, calculation of bone mineral apparent density) dampened the apparent rate of bone loss from most skeletal sites as judged from cross-sectional measurements at baseline. Cross-sectional data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
52
2
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 14 publications
16
52
2
2
Order By: Relevance
“…Even women aged 50-54, among whom we observed the greatest bone loss, experienced a rate of loss of only 1.3% per year. Although this rate is lower than estimates derived from crosssectional studies, 32 it is consistent with the rates of loss reported among women in other longitudinal studies.…”
Section: Discussionsupporting
confidence: 88%
“…Even women aged 50-54, among whom we observed the greatest bone loss, experienced a rate of loss of only 1.3% per year. Although this rate is lower than estimates derived from crosssectional studies, 32 it is consistent with the rates of loss reported among women in other longitudinal studies.…”
Section: Discussionsupporting
confidence: 88%
“…At the distal forearm Rey et al [26] found a T-score reduction of -3.0 SD between 30 and 75 years of age. However, one must keep in mind the limitations of cross-sectional data in assessing bone loss compared with longitudinal evaluation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while men lack the rapid phase of bone loss present at menopause in women, they lose substantial amounts of bone with aging (11)(12)(13)(14). In addition, population-based studies have shown that bone resorption increases with age in Young adult males who cannot produce or respond to estrogen (E) are osteopenic, suggesting that E may regulate bone turnover in men, as well as in women.…”
Section: Introductionmentioning
confidence: 99%